Comparison of Retrograde Intrarenal Surgery and Micro-percutaneous Nephrolithotomy for Kidney Stones 5-10 mm in Diameter - Bayram Güner; Bilal Günaydın (Haseki Tıp Bülteni)

(untitled)
Aim:To compare the results of micro-percutaneous nephrolithotomy (micro-PNL) and retrograde intrarenal surgery (RIRS) for symptomatic renal stones 5-10 mm in diameter.Methods:A total of 86 patients, who underwent RIRS (n=53) and micro-PNL (n=23), were evaluated retrospectively. Urine analysis, serum creatinine level, urine culture and non-contrast computed tomography scan were performed in all patients preoperatively. Kidney stones were opaque in all cases. Unresolved coagulopathy, active urinary infection, morbid obesity, missing data and pregnancy were considered the criteria for exclusion. The groups were compared in terms of operative time, Visual analogue scale score, analgesic requirement, retreatment, transition to other treatment, complication and stone-free rates and length of hospital stay.Results:Both surgical techniques were similar for all parameters except need for analgesics, which was higher in the micro-PNL group (p=0.026). The stone-free rate was 85.7% in the RIRS group and 78.2% in the micro-PNL group (p=0.43).Conclusion:Both methods can be administered as alternative modalities with high success and low complication rates. However, analgesics requirement was higher in micro-PNL group.